Mobilizing and training academic faculty for medical mission: current status and future directions - James D Smith; Roger P Holland; J Dwight Phillips; Sharon A Falkenheimer (Health for All Nations, 2016)
As more mission groups become involved with health care education, by starting medical and nursing schools, postgraduate training programs and paramedical professional training, there is a need to recruit expatriate faculty from high income countries to help start programs as there are few national health care education professionals available in the mission setting in most low- and middle-income countries. This paper outlines the current status and needs for academic faculty in health care education mission settings. A working group of medical educators met in conjunction with the Global Missions Health Conference in November 2015 and discussed the motivational factors which lead Christian academics to volunteer, both short- and long-term in mission settings. The group then looked at barriers to volunteering and made suggestions for future directions and best practices when mobilizing academics from high income countries.